(untitled) (Journal of Plant Disease Sciences, 2017)
Among the major constraints in chilli cultivation, dry root rot caused by Sclerotium rolfsii Sclerotium rolfsii Sacc. is an important one. Ten isolates of collected from various locations were studied for their morphological and cultural characteristics. Radial growth was ranged from 41.17 to 70.67 mm, with sparse colony and peripheral circular growth pattern; however, isolates SrBd and SrAn showed peripheral circular upward end growth. Pigmentation of sclerotia varied from olive brown to dark. The oxalic acid production ranged from 31 mg/ml to 90 mg/ml. Thus the results revealed possibility of existence of variability among S rolfsii, incitant of chilli dry root rot.